Global Governance in The Covid-19 Pandemic Perspective (On the Example of Fiscal Policy Instruments) - Emilia JANKOWSKA-AMBROZIAK; Aneta KARGOL-WASILUK; Mariusz MAK; Marian ZALESKO (Communications of International Proceedings, 2022)
Over two decades of the 21st century abounded in many world-threatening events (the so-called black swans)(i). They made a significant impact on the functioning of society and economy, both internationally and locally. One of such events was the outbreak and spread of the COVID-19 pandemic, and as an effect the so-called coronacrisis. It took a global character, as it covered all countries of our globe, showing the fragility of many civilizational achievements, of faith in the progress and in improvement of living conditions of mankind. The implementation of the concept of global governance may be helpful in neutralizing the consequences of this type of event. The idea of ​​global governance should be understood as a specific set of ways of regulating the problems important for the whole world by institutions (formal and informal) of a public and private nature, where the decision-making body should be a coalition of states, international organizations, non-governmental organizations and other entities acting together to eliminate negative effects of crisis phenomena. It seems that the concept of global governance could significantly contribute to shaping an appropriate fiscal response at the global level in order to eliminate the negative effects of the coronacrisis. Hence, the authors decided to study the importance of global governance in the COVID-19 perspective emphasizing the factors that affect the development of the concept. The methods used in the paper are comparative and statistical data analysis. The authors analyzed governmental and international actions against the pandemic in the fiscal sphere. One of the main conclusions drawn is the fact that the concept of global governance is a developing process in which the rules are never fully fixed and need to be the subject of constant verification.
Keywords: Global Governance; COVID-19 Pandemic; Fiscal Policy; Fiscal Instruments